Jan Deny about phonetics of the turkish language (Eurasian Journal of Philology Science and Education, 2018)
French linguist J.Denny`s phonetics characteristics of the Turkish language had shown in the article, the details of phonetics of the Turkish language had analyzed widely. Phonetics of every language is represented its identity with similarities and differences of sound world, their place in verbal speech, finally, itself language with purposeful complex of the sounds. Internal structure issues of the language is stood on the basis of linguistic knowledge of every linguist. Phonetics of language is noted especially from this succession. In a sense, mastering of every language begins from phonetics and goes to the next level of hierarchical system of the language. J. Denny defines similarity between vowels «a», «o», «ö», «ü» in the turkish language in phonetics of the french language. In the article is also talked about french, arabic, persian acquisitions in the turkish language, is spoken in their adaptation to the turkish language, combination with the grammar of the turkish language. In XVII-XVIII centuries were taken enough acquisitions from the italian language . After II World War it gave it`s place to the english language.